2010
DOI: 10.1007/s11605-009-1149-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polyethylene Glycolic Acid Felt with Fibrin Sealant to Prevent Postoperative Pancreatic Fistula in Pancreatic Surgery

Abstract: In summary, our procedure using PGA felt with fibrin sealant may reduce the risk of severe POPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 24 publications
1
45
1
1
Order By: Relevance
“…They include artificial patches [32], glue applications [21,33], pancreatico-jejunostomies [16,27,28], extra-pancreatic organ patches [16,34,35], and octreotide [36]. Despite these attempts, the occurrence of PF has continued to vex surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…They include artificial patches [32], glue applications [21,33], pancreatico-jejunostomies [16,27,28], extra-pancreatic organ patches [16,34,35], and octreotide [36]. Despite these attempts, the occurrence of PF has continued to vex surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Polyethylene glycolic acid (PGA) felt is a soft and fl exible absorbable nonwoven textile, and is widely used for tissue reinforcement. [7][8][9] Its attachment on a tissue is greatest when applied in combination with fi brin glue. We herein report the impact of using soft coagulation followed by the application of PGA felt and fi brin glue to prevent PF after DP.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, BMI, [6,7,10] thickness, [7,8] and texture [8,11] have been identified as risk factors for POPF after DP. Various efforts to reduce the POPF rate have been attempted, including perioperative treatment with octreotide analog, pasireotide, [12] polyethylene glycolic acid mesh, [13] topical absorbable fibrin sealant patch, [14] pancreaticojejunostomy, [15] falciform ligament patch, [16] prolonged prefiring compression, [17] and seromuscular patch. [18] The method of pancreas stump closure is a major factor in preventing POPF.…”
Section: Discussionmentioning
confidence: 99%